Application of custom-designed oligonucleotide array CGH in 145 patients with autistic spectrum disorders - Wiśniowiecka-Kowalnik, Barbara (Nature Publishing Group, 2013)
Autism spectrum disorders (ASDs) are a heterogeneous group of neurodevelopmental disorders, including childhood autism, atypical autism, and Asperger syndrome, with an estimated prevalence of 1.0–2.5% in the general population. ASDs have a complex multifactorial etiology, with genetic causes being recognized in only 10–20% of cases. Recently, copy-number variants (CNVs) have been shown to contribute to over 10% of ASD cases. We have applied a custom-designed oligonucleotide array comparative genomic hybridization with an exonic coverage of over 1700 genes, including 221 genes known to cause autism and autism candidate genes, in a cohort of 145 patients with ASDs. The patients were classified according to ICD-10 standards and the Childhood Autism Rating Scale protocol into three groups consisting of 45 individuals with and 69 individuals without developmental delay/intellectual disability (DD/ID), and 31 patients, in whom DD/ID could not be excluded. In 12 patients, we have identified 16 copy-number changes, eight (5.5%) of which likely contribute to ASDs. In addition to known recurrent CNVs such as deletions 15q11.2 (BP1-BP2) and 3q13.31 (including DRD3 and ZBTB20), and duplications 15q13.3 and 16p13.11, our analysis revealed two novel genes clinically relevant for ASDs: ARHGAP24 (4q21.23q21.3) and SLC16A7 (12q14.1). Our results further confirm the diagnostic importance of array CGH in detection of CNVs in patients with ASDs and demonstrate that CNVs are an important cause of ASDs as a heterogeneous condition with a variety of contributory genes.